2011
DOI: 10.1021/am200388h
|View full text |Cite
|
Sign up to set email alerts
|

Ti-Doped Indium Tin Oxide Thin Films for Transparent Field-Effect Transistors: Control of Charge-Carrier Density and Crystalline Structure

Abstract: Indium tin oxide (ITO) films are representative transparent conducting oxide media for organic light-emitting diodes, liquid crystal displays, and solar cell applications. Extending the utility of ITO films from passive electrodes to active channel layers in transparent field-effect transistors (FETs), however, has been largely limited because of the materials' high carrier density (>1 × 10(20) cm(-3)), wide band gap, and polycrystalline structure. Here, we demonstrate that control over the cation composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
(29 reference statements)
0
25
0
Order By: Relevance
“…Generally, strong oxygen-binding cations, e.g., X ¼ Y, 18 Ga, 11,19 Ti, 20 and Al, 21 are introduced into In 2 O 3 host as matrix dopants to adjust the carrier concentration. Generally, strong oxygen-binding cations, e.g., X ¼ Y, 18 Ga, 11,19 Ti, 20 and Al, 21 are introduced into In 2 O 3 host as matrix dopants to adjust the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, strong oxygen-binding cations, e.g., X ¼ Y, 18 Ga, 11,19 Ti, 20 and Al, 21 are introduced into In 2 O 3 host as matrix dopants to adjust the carrier concentration. Generally, strong oxygen-binding cations, e.g., X ¼ Y, 18 Ga, 11,19 Ti, 20 and Al, 21 are introduced into In 2 O 3 host as matrix dopants to adjust the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al reported that reduced carrier concentration in the n-type channel material induces higher V th and lower I off , because the channel with lower carrier concentration is more easily depleted [18]. Therefore, these positive shifts of V th and decreased I off are attributable to reductions in electron density in the TFT channels as Al levels increase [2,6,18,19]. In general, oxygen vacancies in SnO x -based materials generate free electrons, which is accompanied by n-type semiconduction [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, intensive research efforts have focused on metal oxide semiconductors, such as ZnO, SnO 2 , In 2 O 5 , and InGaZnO 5 , which have many applications in electronics, sensors, and active matrix displays. Because of their high electron mobility and good transparency, metal oxide semiconductors are especially ideal candidates for the active layers of thin-film transistors (TFTs) [1,2,3,4,5,6,7]. Most metal oxide semiconductors are fabricated via sputtering; their properties are determined by reactions between the injected gases (Ar and O 2 ) and the metals (e.g., In, Sn, Zn, and Ga), typically yielding amorphous, conductive, and transparent materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, both Indium element and Gallium element are toxicant and rare element in the earth, which is not only very expensive but also harmful to our body. In this experiment, we choose Titanium-doped Zinc Oxide as the active layer, as Titanium dopants in Zinc-Oxide are able to suppress the generation of free carriers and obtain an optimal carrier concentration, thus optimizing the electrical performances of the TFTs [7][8][9]. Besides, both Titanium element and Zinc element are non-toxic, cheap and abundant in the earth.…”
Section: Introductionmentioning
confidence: 99%